Tomato: An Overview of Application of Turmeric (Curcuma longa L.), Neem (Azadiratcha indica) on Shelf-Life Extension During Post-Harvest Storing of Tomato (Solanum lycopersicum L.) - Abdulrahman, Hamza; Tukur, Ummu; Umar, Dikko Haliru (Darul Yasin Al Sys, 2024)
Tomato (Solanum lycopersicum) has to be preserved to prevent losses and ameliorate food security. Turmeric (Curcuma longa L.) and neem (Azadirachta indica) extracts are useful to extend shelf life of tomato. This paper performed a review of tomato and use of neem and turmeric for its storage/ preservation. This paper mostly, will discuss the tomatoes under the following headings: history, biological nature, taxonomy, postharvest importance, utilization of neem and turmeric for its storage, economic benefits, and disadvantages of using artificial preservatives.